UCP3 and its putative function: consistencies and controversies. (November 2001) - Harper, M.-E.; Dent, R. M.; Bezaire, V.; Antoniou, A.; Gauthier, A.; Monemdjou, S.; McPherson, R.
Abstract : The physiological function of uncoupling protein 3 (UCP3) is as yet unknown. Based on its 57% homology to UCP1 whose physiologic function is uncoupling and thermogenesis, UCP3 was attributed with the function of mitochondrial uncoupling through proton-leak reactions. UCP3 is expressed selectively in muscle, a tissue in which it has been estimated that proton leak accounts for approx. 50% of resting energy metabolism. Genetic linkage, association and variant studies suggest a role for UCP3 in obesity and/or diabetes. Studies of the heterologous expression of UCP3 in yeast provide support for the idea that UCP3 can uncouple mitochondrial oxidative phosphorylation, but the physiological relevance of these results is questionable. In vitro studies of mitochondria from Ucp3 − − mice provide support, but there are no changes in resting metabolic rate (RMR) of mice. In vivo studies demonstrate increased ATP synthesis, but estimates of substrate oxidation rate indicate no change. Mice that greatly overexpress Ucp3 in muscle have increased RMR. Inconsistent with the function of uncoupling are the observations that fasting results in increased expression of UCP3, but no change in muscle proton leak. Moreover, fasting decreases energy expenditure in muscle. Expression patterns for Ucp3 and lipid-metabolism genes support a physiological role in fatty acid oxidation. Overall, findings support a role for Ucp3 in fatty acid metabolism that may have implications for obesity and/or Type II diabetes.